Aesthetically Appealing Building Integrated Photovoltaic Systems for Net-Zero Energy Buildings. Current Status, Challenges, and Future DevelopmentsA Review - Basher M.K.; Nur-E-Alam M.; Rahman M.M.; Alameh K.; Hinckley S. (MDPI, 2024)
With the sharp increase in global energy demand, industrial and residential buildings are responsible for around 40% of the energy consumed with most of this energy portion being generated by non-renewable sources, which significantly contribute to global warming and environmental hazards. The net-zero energy building (NZEB) concept attempts to solve the global warming issue, whereby a building will produce, on-site, its required energy demand throughout the year from renewable energy sources. This can be achieved by integrating photovoltaic (PV) building materials, called building-integrated photovoltaic (BIPV) modules, throughout the building skin, which simultaneously act as construction materials and energy generators. Currently, architects and builders are inclined to design a building using BIPV modules due to the limited colors available, namely, black or blue, which result in a monotonous building appearance. Therefore, there is an increasing demand/need to develop modern, aesthetically pleasing BIPV green energy products for the use of architects and the construction industry. This review article presents the current stage and future goal of advanced building integrated photovoltaic systems, focusing on the aesthetically appealing BIPV systems, and their applications towards overcoming global challenges and stepping forward to achieve a sustainable green energy building environment. Additionally, we present the summary and outlook for the future development of aesthetically appealing building integrated photovoltaic systems. 2023 by the authors.